Extraction of Coal Liquefaction Residue with Aliphatic Hydrocarbon Solvents and the Separation and Characterization of Extracts by n-Heptane - Yang LIU; Jianbo HUANG; Lunjing YAN; Junjie LIAO; Weiren BAO; Jiancheng WANG; Liping CHANG (Taiyuan Ligong Daxue xuebao, 2022)
The effects of four aliphatic hydrocarbon extractants (n-hexane, cyclohexane, petroleum ether, and n-heptane) on the extraction rate and properties of extracts from coal liquefaction residue were investigated by Soxhlet extraction experiments. The results show that the molecular structure, viscosity, and boiling point of extractants affected extraction rate, and the extraction rates of four extractants were in the following order: cyclohexane, petroleum ether, n-hexane, n-heptane. As for the composition of extracts, the extracts of n-hexane, cyclohexane, and petroleum ether were mainly composed of aliphatic hydrocarbons, while the extracts of n-heptane were dominated by polycyclic aromatic hydrocarbons with a relative content of 94.1%, among which pyrene substances accounted for 53.3%. The n-heptane extracts of coal liquefaction residue were further sequentially eluted by column chromatography, and their compositions were analyzed. As the elution proceeded, the main components in petroleum ether eluate gradually changed from aliphatic hydrocarbons to polycyclic aromatic hydrocarbons, and the ring number of polycyclic aromatic hydrocarbons gradually increased. The petroleum ether/carbon disulfide eluate could be enriched with 59.7% of benzo[ghi]perylene. Later, dibutyl phthalate with a relative content of 50.7% could be enriched by petroleum ether/ethyl acetate as eluent. The separation of different substances in n-heptane extracts was achieved by ethyl acetate and methanol, and the methanol eluate mainly contained lipids, phenols, and alcohols. The separation and detection of extracts were basically achieved by this method.